RELIGIONS AND NATIONAL INTEGRATION - Manickam, Thomas (Journal of Dharma, 1983)
Integration of the forces and sources of life, ideas and ideologies is essential for peace, prosperity and progress of any nation. In the case of nations which are historically and structurally constituted of diverse ethnic or racial groups, numerous and varied religious denominations, multilingual geographical areas, widely uneven ecnomic social stratao, and opposing political ideologies, integration becomes an urgency even for sheer survival especially in the context of imminent foreign threats. Most of the nations of the present day world, including the super powers, have to face this challenge of consolidating the various forces operating both overtly and covertly in their internal systems. This is the quintessence of integration which has as its aims the achievement of peace, harmony, cohesion, security, development and welfare.